Motivation in education at a time of global change : theory, research, and implications for practice - Gonida, Eleftheria N.; Serra Lemos, Marina (Advances in motivation and achievement ;, 2019)
Economic, social and political disruption, financial recession, international migration and rapid technological advancements have produced major changes throughout the world regarding the availability and access to knowledge, human communication, social relationships, learning and education. As socioeconomic, sociodemographic and sociocultural conditions are constantly changing in parallel with rapid scientific and technological progress, learning environments are also evolving. The increased complexity of educational processes calls for new research and theoretical inquiry to address how these global changes affect education, schools and academic learning. This volume in the Advances in Motivation and Achievement Series is dedicated to the role of motivation in that process. The fundamental assumption of the volume is that, on the one hand, change and challenge have a significant impact on students' and educators' motivation to learn and achieve and, on the other hand, motivation can have a significant impact on students' and educators' capacity to cope with change and challenge effectively.This book opens up a dialogue on how to support achievement motivation in challenging times as a means for successful academic trajectories and positive adaptation to school. Internationally leading researchers provide a critical understanding of the role of current motivational theories during unsettling times, discuss a number of challenges affecting motivation in education, and indicate potential implications of motivational theory and research for educational practice.- Resumé vydavatel